Image processing with nonseparable multiwavelets - Ruedín, Ana M. C. (2001)
In a general context we introduce image processing with 1-dimensional wavelets and show the diferences with nonseparable 2-dimensional wavelets having quincunx decimation, in the first place, and with balanced nonseparable 2-dimensional multiwavelets, in the second place. All of them are orthogonal. Formulae for analysis and synthesis are given for the latter. The first steps are illustrated with images. The decomposition of the original image into 2 input images is explained. We illustrate with examples 2 applications: zoom-in (interpolation) and compression of images.